Validitas dan Reliabilitas Instrumen Prokrastinasi Akademik dan Motivasi Berprestasi Mahasiswa : Penelitian - Putri Ayu, Siska; Fadhilah Syafwar; Irman; Ryan Hidayat Rafiola (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the validity and reliability of two psychological scales developed to measure academic procrastination and achievement motivation among university students. The validity of the instruments was assessed using Pearson Product-Moment correlation, while internal consistency reliability was tested using Cronbach’s Alpha coefficient. A pilot study was conducted with a sample of 20 students outside the main study program to ensure the instruments' objectivity. The results showed that out of 28 items on the academic procrastination achievement motivation scale, 21 items were valid, with a reliability score of α =0.872. Meanwhile, the acheivement motivation academic procrastination scale consisted of 40 items, of which 32 items were valid, and the reliability coefficient was α = 0.883. These findings indicate that both instruments have strong psychometric properties and are suitable for use in psychological and educational research. The study highlights the importance of instrument development procedures, including item analysis and pre-testing, to ensure accurate and consistent measurement.